2020
DOI: 10.1002/ecm.1404
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying water requirements of African ungulates through a combination of functional traits

Abstract: Citation: Kihwele, E. S., V. Mchomvu, N. Owen-Smith, R. S. Hetem, M. C. Hutchinson, A. B. Potter, H. Olff, and M. P. Veldhuis. 2020. Quantifying water requirements of African ungulates through a combination of functional traits. Ecological Monographs 90(2):Abstract. Climate and land use change modify surface water availability in African savannas. Surface water is a key resource for both wildlife and livestock and its spatial and temporal distribution is important for understanding the composition of large her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 44 publications
4
32
0
Order By: Relevance
“…Among the large ungulates inhabiting the Kalahari region, the arid-adapted gemsbok (or South African oryx; Oryx gazella gazella ) appears to possess a number of fixed functional traits allowing it to conserve body water and cope with the dry conditions 8 . For example, an increased relative medullary thickness may promote the production of concentrated urine, and a relatively large surface area to volume ratio of the spiral and distal colon may allow for more water to be absorbed, reducing moisture loss in dung 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the large ungulates inhabiting the Kalahari region, the arid-adapted gemsbok (or South African oryx; Oryx gazella gazella ) appears to possess a number of fixed functional traits allowing it to conserve body water and cope with the dry conditions 8 . For example, an increased relative medullary thickness may promote the production of concentrated urine, and a relatively large surface area to volume ratio of the spiral and distal colon may allow for more water to be absorbed, reducing moisture loss in dung 9 .…”
Section: Introductionmentioning
confidence: 99%
“…We further expected wildebeest to select cooler microclimates and spend a greater proportion of their time in these cooler shaded microclimates to reduce heat loads during the heat of the day, which may result in reduced daytime activity. With fewer fixed functional traits to conserve body water 8 , we expected that wildebeest would spend more time travelling to diminishing surface water, thereby increasing total 24 h activity compared to gemsbok, especially during a drought season compared to a non-drought hot and dry season.…”
Section: Introductionmentioning
confidence: 99%
“…Our study considered impacts of ephemeral water only on buffalo and elephants. Previous research has shown that herbivores fall along a gradient of water dependence (Redfern et al 2003, Kihwele et al 2020). We would therefore hypothesize that browsers like kudu and giraffe, which are expected to be less water‐dependent than grazers (Redfern et al 2003), would show weaker relationships among ephemeral water and distribution/movements if subjected to similar analyses as performed here.…”
Section: Discussionmentioning
confidence: 99%
“…We urge users to report errors or updates on newly published data for integration into HerbiTraits by filing an Issue on our GitHub ( https://github.com/MegaPast2Future/HerbiTraits ) repository page, or by emailing the corresponding authors. Furthermore, the GitHub ( https://github.com/MegaPast2Future/HerbiTraits ) page includes an incomplete trait file, which contains other ecologically relevant traits, such as adaptations for digging and free water dependence 60 . These traits remain unavailable for many taxa, but provide a starting point for further data collection and analysis.…”
Section: Technical Validationmentioning
confidence: 99%